Populus nigra L. as a bioindicator of atmospheric trace element pollution and potential toxic impacts on human and ecosystem. (December 2018) - Yalaltdinova, Albina; Kim, Junbeum; Baranovskaya, Natalia; Rikhvanov, Leonid
Graphical abstract: Highlights: Populus nigra is a suitable bioindicator of atmospheric pollution and toxic impact. Ag, As, Na, Sb, Sr, Ta, U, Zn concentrate at higher levels. Highest potential toxic effect is observed near to the Northern Industrial Zone. Zinc emissions contribute most to the toxicity index (about 99%). Abstract: Changes in the environment like atmospheric trace element pollution can be mirrored in the elemental composition of indicator plants. They can contribute to distinguishing the degree of pollution, allocate sources of pollution, and identify their impact areas and polluting ingredients. However, ideally, the study should not be limited by these results. We should make more use of them to predict potential negative effects on the ecosystems and human health. In this research, an integrated study was implemented in Ust-Kamenogorsk city (Kazakhstan), in a territory with multicomponent, multifactor man-made impacts. Analyzing black poplar leaves we identified that Ag, As, Na, Sb, Sr, Ta, U, Zn concentrate at higher levels when compared with literature, their average contents in the dry weight of leaves are 0.08, 0.38, 936, 0.32, 193, 0.01, 0.08, 468 mg/kg respectively. We were able to show that the main source of Ag, Au, Sb, Zn is the lead-zinc plant "Kazzinc", while Be, Ta, U came from the Ulba metallurgical plant. As a result, we suggested that air pollution is the main parameter influencing the change of elemental composition of poplar leaves. Applying the results in life cycle impact assessment (LCIA) methodology also allows us to indicate not only the degree of contamination, but also to predict the degree of toxic exposure. The highest toxic effect on humans and ecosystems is observed in the impact zone of both companies, while zinc emissions contribute most to the toxicity index (about 99%).